Electrochemical impedance spectroscopy study of lithium–sulfur batteries: Useful technique to reveal the Li/S electrochemical mechanism. (1st November 2020) - Waluś, Sylwia; Barchasz, Céline; Bouchet, Renaud; Alloin, Fannie
Abstract: Electrochemical impedance spectroscopy (EIS) study was done in order to go deeper into the electrochemical processes of Li/S battery in a common CR2032 coin-type cell. In order to separate the contributions of each electrode (i. e. lithium negative electrode and sulfur composite positive electrode), impedance measurements on symmetrical cells consisting of two previously cycled electrodes was used. This methodology enables to propose an overall interpretation of the different electrochemical phenomena present during cycling. Low temperature tests were also applied, which brought fruitful information concerning the kinetics of the reactions and allowed to confirm the chemical-physical interpretations performed on the cell cycled at 25°C.